Liberia vs Cote D'Ivoire (soccer match) (African Knowledges and the History Publication since the 1970s, 1986)
CEDAO Cup match between Liberia and Cote D'Ivoire, also the launching of the new Samuel Kanyon Doe Sports Complex.
Keywords: Sports